Overexpression of microRna-200c in CD44+CD133+ CSCS inhibits the cellular migratory and invasion as well as tumorigenicity in mice - Dou, J.; He, X. F.; Cao, W. H.; Zhao, F. S.; Wang, X. Y.; Liu, Y. R.; Wang, J. (Cellular and Molecular Biology, 2013)
Cancer stem cells (CSCs) are believed to be responsible for drug resistance, metastasis of tumors. To investigate the biological characteristics of CD44+CD133+CSCs with over- expressing microRNA-200c (miR-200c), and to provide evidences for miR-200c as a tumor suppressor to treat melanoma. CD44+CD133+CSCs were isolated from the mouse melanoma B16F10 cell line by using immune magnetic activated cell sorting. The lentivirus miR-200c was transduced into the cells, and the effect of miR-200c overexpression on the biological characteristics of B16F10 CD44+ CD133+CSCs was analyzed by a series assays. The stable overexpression of miR-200c in B16F10 CD44+CD133+CSCs obviously resulted in downregulation of zinc-finger E-box binding homeobox 1 expression, reduction of the cell proliferation, colony forming, cell migratory and invasion ability in vitro as well as tumorigenicity in vivo compared with those of the B16F10 cells and B16F10 non-CD44+ CD133+CSCs. These findings suggest that the miR-200c overexpression as a novel strategy to target therapy of melanoma CSCs.